Leadership efficacy in youth football: Athletes and coaches perspective - Gomes, A. Rui (2022)
According to the Leadership Efficacy Model, leadership efficacy depends on leaders’ tendency to make linear relationships between leadership philosophy, practice, and criteria (i.e., congruence of leadership cycles); if leaders make these linear relationships by using the optimal leadership profile; and if leaders considers the antecedent factors of leadership (favourability of conditions for leadership). This study compared the perceptions of athletes and their coaches regarding leadership cycles, and tested the moderator role of optimal leadership profile and leadership favourability in the relationship between leadership cycles and leadership efficacy. The study included 92 football athletes (ages under-17 and under-19) and respective coaches (n = 5). It was evaluated leadership cycles, leadership styles, leadership favourability, and sport performance perception. Athletes and coaches agreed on coaches’ need to increase leadership cycles. Regression analyses confirmed that leadership congruency predicts higher perceptions of team performance in athletes. Moreover, optimal leadership profile and higher leadership favourability were associated with higher team and individual performance. However, these two factors did not moderate the relationship between leadership congruency and efficacy. Coaches should clarify better their leadership cycles and they have advantages in using the optimal leadership profile and considering the antecedent factors of leadership in order to establish the leadership cycles.